Migrant Precarity in Asia: 'Networks of Labour Activism' for a Rights‐based Governance of Migration. Issue 5 (5th September 2017) - Piper, Nicola; Rosewarne, Stuart; Withers, Matt
ABSTRACT: This article uses migrant precarity as a lens through which to analyse the issue of mobilization for migrants' rights by civil society. Such mobilization efforts are vital in light of the emergence of global migration governance, which tends to actively constrain considerations for migrants' human and labour rights. Asia's temporary migrants have been identified as a particularly precarious group of workers due to their specific position within the international division of labour, one that is defined by poorly‐ or unregulated work with insecure legal and residential status. Moreover, with local employment in countries of origin often characterized by informal employment, poor working conditions and unsustainable livelihoods, migrant workers are caught within a protracted precarity that spans life at home and abroad. Stronger normative and organizational links between global migration governance and migrant rights movements are needed to advance decent work agendas within countries of destination, as well as in countries of origin.